2021
DOI: 10.1108/tqm-05-2020-0117
|View full text |Cite
|
Sign up to set email alerts
|

The impact of service excellence and service innovation on organisational reputation: quantitative evidence from Jordanian public sector

Abstract: PurposeThe aim of this paper is the identification of the impacts that innovation and service excellence have upon organisational reputation within public sector organisations in Jordan.Design/methodology/approachAn approach was adopted that was quantitative with a questionnaire designed that was to be self-administrated for the primary data collection. In total, there was distribution of 600 questionnaires from which 556 were retrieved with a high rate of response (92.7%).FindingsThrough analysis of the data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Adhocracy culture is viewed as a culture that fosters innovation (Hamzah et al, 2022). Moreover, Aladwan and Alshami (2021) found that invention significantly impacts a company's reputation. Hence the following hypothesis is proposed: H5: Clan culture has a positive effect on a firm reputation.…”
Section: Organizational Culture On Firm Reputationmentioning
confidence: 99%
“…Adhocracy culture is viewed as a culture that fosters innovation (Hamzah et al, 2022). Moreover, Aladwan and Alshami (2021) found that invention significantly impacts a company's reputation. Hence the following hypothesis is proposed: H5: Clan culture has a positive effect on a firm reputation.…”
Section: Organizational Culture On Firm Reputationmentioning
confidence: 99%
“…Due to such market turbulence, organizations have to be innovative both in product and service delivery for their sustainability (Qiu et al, 2020). Thus, through service innovation and service excellence, organization can improve their image and as a consequence, share in the market (Aladwan and Alshami, 2021).…”
Section: Market Pressure and Competitionmentioning
confidence: 99%
“…The innovations in service delivery provide customers with superior values and improve their satisfaction (Kindstroem et al, 2012). In the prior literature, service innovation has been regarded as the significant capability for enabling firms to increase their performance and enhance brand reputation (Aladwan & Alshami, 2021;Eggert et al, 2014;Feng et al, 2020;Lin, 2013). Certain studies found that service innovation has a positive impact on corporate reputation (Ganesan & Sridhar, 2016;Sridhar & Mehta, 2018).…”
Section: Innovation Capabilitiesmentioning
confidence: 99%